Stress-Induced Enhancement of Ethanol Intake in C57BL/6J Mice with a History of Chronic Ethanol Exposure: Involvement of Kappa Opioid Receptors - Anderson, Rachel I.; Lopez, Marcelo F.; Becker, Howard C. (Frontiers in Cellular Neuroscience, 2016)
Our laboratory has previously demonstrated that daily forced swim stress (FSS) prior to ethanol drinking sessions facilitates enhanced ethanol consumption in mice with a history of chronic intermittent ethanol (CIE) vapor exposure without altering ethanol intake in air-exposed controls. Because both stress and chronic ethanol exposure have been shown to activate the dynorphin/kappa opioid receptor (KOR) system, the present study was designed to explore a potential role for KORs in modulating stress effects on ethanol consumption in the CIE model of dependence and relapse drinking. After stable baseline ethanol intake was established in adult male C57BL/6J mice, subjects received chronic intermittent exposure (16 hr/day x 4 days/week) to ethanol vapor (CIE group) or air (CTL group). Weekly cycles of inhalation exposure were alternated with 5-day limited access drinking tests (1 hour access to 15% ethanol). Experiment 1 compared effects of daily FSS and KOR activation on ethanol consumption. CIE and CTL mice were either exposed to FSS (10 min), the KOR agonist U50,488 (5 mg/kg), or a vehicle injection (non-stressed condition) prior to each daily drinking session during test weeks. FSS selectively increased drinking in CIE mice. U50,488 mimicked this effect in CIE mice, but also increased drinking in CTL mice. Experiment 2 assessed effects of KOR blockade on stress-induced drinking in CIE and CTL mice. Stressed and non-stressed mice were administered the short-acting KOR antagonist LY2444296 (0 or 5 mg/kg) 30 min prior to each drinking session during test weeks. FSS selectively increased ethanol consumption in CIE mice, an effect that was abolished by LY2444296 pretreatment. In Experiment 3, CIE and CTL mice were administered one of four doses of U50,488 (0,1.25, 2.5, 5.0 mg/kg) one hour prior to each daily drinking test (in lieu of FSS). All doses of U50,488 increased ethanol consumption in both CIE and CTL mice. The U50,488-induced increase in drinking was blocked by LY2444296. Our results demonstrate that the KOR system contributes to the stress enhancement of ethanol intake in mice with a history of chronic ethanol exposure.